If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (Y + 6)(y + -2) = -7 Reorder the terms: (6 + Y)(y + -2) = -7 Reorder the terms: (6 + Y)(-2 + y) = -7 Multiply (6 + Y) * (-2 + y) (6(-2 + y) + Y(-2 + y)) = -7 ((-2 * 6 + y * 6) + Y(-2 + y)) = -7 ((-12 + 6y) + Y(-2 + y)) = -7 (-12 + 6y + (-2 * Y + y * Y)) = -7 (-12 + 6y + (-2Y + yY)) = -7 Reorder the terms: (-12 + -2Y + 6y + yY) = -7 (-12 + -2Y + 6y + yY) = -7 Solving -12 + -2Y + 6y + yY = -7 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '12' to each side of the equation. -12 + -2Y + 6y + 12 + yY = -7 + 12 Reorder the terms: -12 + 12 + -2Y + 6y + yY = -7 + 12 Combine like terms: -12 + 12 = 0 0 + -2Y + 6y + yY = -7 + 12 -2Y + 6y + yY = -7 + 12 Combine like terms: -7 + 12 = 5 -2Y + 6y + yY = 5 Add '-6y' to each side of the equation. -2Y + 6y + -6y + yY = 5 + -6y Combine like terms: 6y + -6y = 0 -2Y + 0 + yY = 5 + -6y -2Y + yY = 5 + -6y Reorder the terms: -5 + -2Y + 6y + yY = 5 + -6y + -5 + 6y Reorder the terms: -5 + -2Y + 6y + yY = 5 + -5 + -6y + 6y Combine like terms: 5 + -5 = 0 -5 + -2Y + 6y + yY = 0 + -6y + 6y -5 + -2Y + 6y + yY = -6y + 6y Combine like terms: -6y + 6y = 0 -5 + -2Y + 6y + yY = 0 The solution to this equation could not be determined.
| 4y^4-13y^2+9=0 | | 9-5z=12-(6a+7) | | 11x-3=5n+9 | | 0.7143x+15+0.6429+-9= | | 12.1x+x-7.2=5.3 | | (y+6)(y+2)=-7 | | x(x-3)+2(x-3)=0 | | 10x^2+64x+60=0 | | 12x-83=6x+21 | | 2a+3/3=5 | | 186=-3x+6(-3x+3) | | 111111*111111=x | | 12345*67890=3x-4y+67 | | C=3.5+6m | | -7-2n=10 | | 4x-32=58-2x | | -12(x+2)=-14x+2 | | 2(g-2)-4=2 | | -7n-2=10 | | C=6m+3.5 | | 6789*3366=3x-4y | | x^2+x+3=6x+3 | | 2(8x+2)=-17-2x-3x | | (2x^4)-(5x^3)-(76x^2)-(96x)=0 | | N^2-7n-25=0 | | 5(b-2)=b+10 | | -(4p-4)=-29+7p | | 8r-14=22+4r | | -(4p-4)=-2+7p | | 2t-10=-10+5t | | 6(-2r+2)=12-2r | | 3x=98 |